Household characteristics and market participation competence of smallholder farmers supplying cassava to starch processors in Nigeria - Ojiako, I.A.; Tarawali, G.; Okechukwu, R.U.; Chianu, Jonas N. (2017)
The household head characteristics of smallholder cassava farmers supplying raw materials to the major commercial starch processors in Nigeria were examined alongside their market participation categories. A multi-stage random sampling technique was used to select 96 farmers working in clusters in the eight cassava producing states. Data were analyzed using a combination of descriptive and inferential statistics, including the use of independent sample t-test technique to compare farmer's characteristics for the farmers' market participation categories. Results revealed that majority of the farmers were farming for subsistence with only 19.80% selling up to 50% of their farm produce as against 80.20% who sold less. Average mean values were found to be higher for the high market participants compared with the low participants for the age, farming experiences, education, farm size, gender, marital status, household size, training, season of harvesting and fertilizer use, but lower for use of credit, improved cassava variety, harvesting method, farming time devotion, and road access. Only farm size, gender and harvesting season at p<0.01 level and training at p<0.05 level were found to be statistically significant in distinguishing the high and low market participation categories. Policies and programmes aimed at promoting market participation among cassava farmers in Nigeria should be more impactful if directed at these significant factors.